Molecular characterization and detection of Babesia canis vogeli in asymptomatic roaming dogs in Chiang Mai, Thailand - Buddhachat K. (2014)
The purpose of this study is to detect Babesia canis by using 18S rDNA amplification in order to confirm the presence of the agents and to characterize molecularly the Thai B. canis. Three sets of primers, a Babesia canis-specific primer (BcSP), Piroplasm-specific primer (PSP) and Babesia species-specific primer (BsSP), were tested for sensitivity. The results showed that BcSP and PSP were 50 times more sensitive than BsSP. Both BcSP and PSP were specific enough to detect this parasite in asymptomatic dogs. Peripheral blood samples were collected from 102 asymptomatic dogs residing in Chiang Mai and assayed with a light microscope and PCR by using BcSP and PSP primers. As a result, fourteen (13.72%) and nine (8.82%) peripheral blood samples were positive by PCR using BcSP and PSP, respectively. No positive samples were found from blood smears. Moreover, Phylogenetic analysis demonstrated that Thai B. canis was subspecies vogeli. Homology sequencing of the partial 18S rDNA gene of Thai B. canis vogeli (accession number JF825145) compared to other sequences from different regions was identical to that found in China, Japan, Venezuela and Brazil with 99.86% homology. Our work represents the first molecular characterization of Thai B. canis by using the 18S rDNA gene.